12t=9(t-15)

Simple and best practice solution for 12t=9(t-15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12t=9(t-15) equation:


Simplifying
12t = 9(t + -15)

Reorder the terms:
12t = 9(-15 + t)
12t = (-15 * 9 + t * 9)
12t = (-135 + 9t)

Solving
12t = -135 + 9t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-9t' to each side of the equation.
12t + -9t = -135 + 9t + -9t

Combine like terms: 12t + -9t = 3t
3t = -135 + 9t + -9t

Combine like terms: 9t + -9t = 0
3t = -135 + 0
3t = -135

Divide each side by '3'.
t = -45

Simplifying
t = -45

See similar equations:

| 10.60+106= | | r^4=1024 | | 4u^2+4u-32= | | 9=r(r-8) | | 10.60-106= | | 7-(3n-3)=2-4n | | 2(x+2)+4x=x+5 | | 7r^2-10=25 | | 7x+8=x^2 | | 9(y+9)=8y-7 | | 6b^2-11b-35=0 | | -(b+1)=10-b | | 6a+3=-3(2a-1) | | 4x-10-6x+3=5-9x-7+2x | | 1500+8x=1500+12x | | 106-21.20= | | 6p=3(t+4)-t | | 8x^2-13=-8 | | 22-(x+5)=7x-7 | | 4x-14-6x+4=6-8x-8+2x | | 3y-5=5y+4 | | 6m^2+5m-4= | | 5d-d= | | 21.20-106= | | 4m^2+5=-57 | | 4x+39+12x-17=180 | | x+x+11=83 | | 7y-13-4y+8=0 | | A+1=37+a | | 7x^2+0.5x=0 | | 6x-5=18x+1 | | -20+17g=1-g |

Equations solver categories